2006
DOI: 10.1109/jdt.2005.862018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dual Coplanar Electrodes on Mercury-Free Flat Fluorescent Lamps for Liquid Crystal Display

Abstract: The effects of dual coplanar electrodes on a Hg-free flat fluorescent lamp were studied. For a dual coplanar lamp, brightness and efficacy were improved by 80% compared to a conventional coplanar lamp. The improvement is regarded as the result of reduced diffusion loss and the effective usage of the discharge volume in the dual coplanar lamps. An efficacy of 35.9 lm/w (14900 cd/m 2) was achieved for 250 torr of a Xe(30%)/Ne(70%) gas mixture, by a 20-kHz ac pulse driving.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The simple transmission geometry adopted for these initial studies is also far from optimal and engineering the phosphor/microplasma coupling geometry as well as the voltage waveform will undoubtedly yield significant improvements in both brightness and efficacy. We note that efficacies >30 lm W −1 with luminance values almost an order of magnitude larger (approaching 15 000 cd m −2 ) than those reported here have appeared recently in the literature [21] for Hg-free lamps employing a Ne/20%Xe mixture, but such fluorescent lamp structures are thick and require driving voltages in the 1-3 kV range. Similar results at considerably reduced excitation voltages are expected to be feasible with large area, microcavity lamp technology.…”
Section: Discussionmentioning
confidence: 38%
“…The simple transmission geometry adopted for these initial studies is also far from optimal and engineering the phosphor/microplasma coupling geometry as well as the voltage waveform will undoubtedly yield significant improvements in both brightness and efficacy. We note that efficacies >30 lm W −1 with luminance values almost an order of magnitude larger (approaching 15 000 cd m −2 ) than those reported here have appeared recently in the literature [21] for Hg-free lamps employing a Ne/20%Xe mixture, but such fluorescent lamp structures are thick and require driving voltages in the 1-3 kV range. Similar results at considerably reduced excitation voltages are expected to be feasible with large area, microcavity lamp technology.…”
Section: Discussionmentioning
confidence: 38%
“…In principle, the FFL structure in this study is similar to the flat fluorescent lamps reported by Lee et al, which consist of two glass substrates and external electrodes. [1][2][3][4][5][6] Our flexible lamp consists of two plastic substrates, i.e., bottom and top substrates, and a plastic barrier layer actually acting as a spacer between the two plastic substrates. The ITO film deposited on plastic substrates has been used as external electrodes by placement on the outer surfaces of the lamp.…”
Section: Introductionmentioning
confidence: 99%
“…In order to simplify the structure and reduce the production cost of a large BLU, intense efforts have been focused on the development of flat fluorescent lamps (FFLs) since late 1990s. [5][6][7][8][9] Both Hg 5) and Hg-free (using Xe gas) 6,10) FFLs were developed during the last decade. For the development of a large area FFL with high efficiency and low cost, it is necessary to understand the discharge phenomena inside the FFL.…”
Section: Introductionmentioning
confidence: 99%
“…18) They showed two-dimensional time-varying charged particle densities and resonant and metastable neutral densities in an electrodeless lamp considering radiation trapping and various Hg reactions with Ar. Park et al 9) displayed the electron and the resonant neutral densities inside Hg-free FFL lamps for LCD BLU.…”
Section: Introductionmentioning
confidence: 99%